CODE-SWITCHING IN BILINGUAL COMMUNITIES - Turdaliyeva Malohat; Khakimbayeva O.K. (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
Many linguists believe that nearly two-thirds of the world’s population can be considered bilingual to some extent. This shows how common bilingualism has become in modern society. One important feature of bilingual communication is code-switching, which is a complex linguistic phenomenon. It refers to the use of two or more languages within the same conversation. In most cases, speakers switch languages unconsciously, following certain patterns and rules rather than doing it randomly. Code-switching helps bilingual express ideas more effectively and share meanings that may not be fully conveyed in just one language. This article briefly discusses bilingualism and examines code-switching in detail, focusing on its functions, benefits and limitations.